Enhancing critical thinking and academic achievement through different learning - Usman, Ali; Agustina, Lady; Bahri, Arsad (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research examines the impact of implementing different learning models on students’ critical thinking abilities (CTS) with different academic achievements. This research was a quasi-experiment and involved 134 high school students in Jember. Research classes are divided into project-based learning (PjBL) and conventional learning, then divided based on academic achievement, namely high and low. Data was collected using essay exams supported by the CTS assessment rubric. Information was analyzed using analysis of covariance (ANCOVA) and continued with the least significant difference (LSD) test. The research results show that i) there is a significant difference in the development of CTS between students who follow the PjBL learning model and students who follow conventional learning; ii) there are differences in CTS development between high and low-achieving students; and iii) there is an interaction between the learning model and student academic achievement which influences the development of CTS. Based on these findings, it can be interpreted that the PjBL learning model effectively increases the development of CTS in high and low-achieving students, especially in low-achieving students. The PjBL learning model encourages students to be active, think critically, work together and solve problems. Teachers can improve the critical thinking skills of students with low academic abilities through the PjBL learning model.